2006
DOI: 10.5005/jcdp-7-2-71
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of the Inferior Dental Canal to the Roots of Impacted Mandibular Third Molars in Jordanian Population

Abstract: Objective: The aim of this study was to evaluate the topographic relationship between the inferior dental canals (IDCs) and the roots of impacted mandibular third molars. Methods:Preoperative orthopantomograms (OPGs) were examined and the proximity of the IDC to the roots of impacted mandibular third molars was categorized into the following: groups: superimposition, adjacent, perforation, grooving, notching, or none. The categories notching, grooving, and perforation were regrouped together and called the tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
24
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 24 publications
13
24
4
Order By: Relevance
“…Present study is not in agreement with study of Hazza'a et al [10] as they found maximum number of vertically placed third molars with superimposed relations, followed by vertically placed third molars with adjacent relations, then mesioangularly placed third molars with superimposed relations and mesioangularly placed third molars with grooving relations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Present study is not in agreement with study of Hazza'a et al [10] as they found maximum number of vertically placed third molars with superimposed relations, followed by vertically placed third molars with adjacent relations, then mesioangularly placed third molars with superimposed relations and mesioangularly placed third molars with grooving relations.…”
Section: Discussioncontrasting
confidence: 99%
“…For gender distribution this study is in accordance with study of Hazza'a et al [10] However, studies of Linden et al, Hattab et al, Yamaoka et al, Sandhu and Kapila, and Odusanya and Abayomi showed female predominance [11, 1316]. This lack of definitive sex predominance in the third molar impaction raised the question against Hellmen's statement that the jaws of the females stop growing when third molar just begin to erupt, whereas in males the growth of the jaws continues beyond the time of third molar [14].…”
Section: Discussionsupporting
confidence: 92%
“…7 In the present study, there was no statistically significant sex distribution of impacted third molars. This is in accordance with observations made by Montelius, 3 Hazza et al, 19 Gupta et al 7 and Padhye et at. 2 However, results of Hellman 20 showed female predominance.…”
Section: Discussionsupporting
confidence: 94%
“…Same results were obtained by Hattab et al Level and Padhye et al, 2 Hazza et al 19 and Gupta et al 7 found that the highest proportion of impacted third molars was in vertical position, followed by mesioangular and distoangular. Furthermore, Richardson 23 found that the highest number of impacted third molars was in horizontal position.…”
Section: Discussionsupporting
confidence: 76%
“…The literature shows that tooth impaction is a frequent phenomenon; 3–14 however, there is considerable variation in the prevalence and distribution of impacted teeth in different regions of the jaw 4–14 . Factors affecting the prevalence include the selected age group, timing of dental eruption, and the radiographic criteria for dental development and eruption.…”
Section: Introductionmentioning
confidence: 99%